Butyrate and obesity: Current research status and future prospect - Peng, Ke; Dong, Wenjie; Luo, Taimin; Tang, Hui; Zhu, Wanlong; Huang, Yilan; Yang, Xuping (Frontiers in Endocrinology, 2023)
Over the past few decades, increasing prevalence of obesity caused an enormous medical, social, and economic burden. As the sixth most important risk factor contributing to the overall burden of disease worldwide, obesity not only directly harms human body, but also leads to many chronic diseases such as diabetes, cardiovascular diseases (CVD), nonalcoholic fatty liver disease (NAFLD), and mental illness. Weight loss is still one of the most effective strategies against obesity and related disorders. Recently, the link between intestinal microflora and metabolic health has been constantly established. Butyrate, a four-carbon short-chain fatty acid, is a major metabolite of the gut microbiota that has many beneficial effects on metabolic health. The anti-obesity activity of butyrate has been demonstrated, but its mechanisms of action have not been fully described. This review summarizes current knowledge of butyrate, including its production, absorption, distribution, metabolism, and the effect and mechanisms involved in weight loss and obesity-related diseases. The aim was to contribute to and advance our understanding of butyrate and its role in obesity. Further exploration of butyrate and its pathway may help to identify new obesity treatments.